PENGARUH ORIENTASI PELAYANAN DAN BAURAN PEMASARAN TERHADAP KEPUASAN PELANGGAN PADA UD. MAJU KENDARI - Azis Muthalib, Dzulfikri; Azis, Muh. Irfandy; Muthalib, Abd. Aziz; N, Ismail Khalid (JIM : Journal Of International Management, 2022)
This study wants to see how the influence of service orientation and marketing mix on customer satisfaction at UD. Maju Kendari. The research sample was 78 customers at UD. Maju Kendari. This study uses multiple linear regression analysis. The significance value is 0.000 which means it is smaller than the value of ? = 0.05, so statistically the variables of service orientation (X1) and marketing mix (X2) simultaneously (together) have a significant effect on customer satisfaction (Y) at the 95% confidence level. The R2 (R-Square) value is 0.897. The R value (correlation coefficient number) of 0.947 indicates that the closeness of the direct relationship between the service orientation variable (X1) and the marketing mix (X2) to customer satisfaction (Y) is 94.7%. After the data is processed, the results are obtained: (1) The higher the service orientation and marketing mix, the higher the customer satisfaction at UD. Maju Kendari. (2) The higher the service orientation, the higher the customer satisfaction at UD. Maju Kendari. (3) the higher the marketing mix, the higher the customer satisfaction at UD. Maju Kendari.